Does breakfast skipping alter the serum lipids of university students? - Shazia Parveen Solangi; Naseem Aslam Channa; Amna Yasin Awan; Muhammad Haneef Mugheri; Zeba Hussain Soomro; Lubna Noorani (BMC Nutrition)
Abstract Background Breakfast is the first meal of the day which is very important in student’s health. The present study was undertaken to explore the role of breakfast skipping in altering the serum lipids of university students. In this case-control study, university students from various disciplines at Shah Abdul Latif University, Khairpur, Pakistan were selected from January 2021 to August 2023 after obtaining written informed consent. Methods Four hundred fifty university students (450) were selected, among them, 158 were Breakfast Skippers (BS) and 292 were breakfast non-skippers (BNS). Of the total, 256 were males and 194 were females with age range of 18–25 years. All participants were enquired about their soci-demographic characteristics and the intake of breakfast during last 3 months. Blood samples were also collected for the serum lipids analysis on auto analyzer ADVIA 1800 S. p-value < 0.05 was kept as level of significant at 95% confidence interval. Results We found 292 (60.9%) BNS and 158 (39.1%) BS university students out of 450 university students. Of these, 49.3% were males and 50.7% were female students. Most of the BS (56.9%) had normal weight and 22–23 were the peak age group of breakfast skippers. We found significant variation among age groups for triglycerides (TG), high density lipoprotein cholesterol (HDL-C) and low density lipoprotein cholesterol (LDL-C) in BS. The total cholesterol (TC), TG, LDL-C, very low density lipoprotein cholesterol (VLDL-C), and total lipids (TL) were significantly increased in the BS in comparison to BNS. Increased levels of TG, VLDL-C and TL were detected in male BS compared to male BNS, whereas, reverse was true for HDL-C. the significant higher levels ofTC, HDL-C, LDL-C and TL were found in female BS in comparison to BNS. Conclusion In conclusion, the significantly highest concentrations of TC, TG, LDL-C, VLDL-C, and TL are found in the BS compared to BNS. We are fully aware of the fact that the university student’s age group is not involved in lipids related diseases, because the lipid related diseases are the signature diseases of elderly population. Hence, if university students don’t have any other medical condition directly or indirectly involved in affecting serum lipids, then the breakfast skipping may be responsible for altering the serum lipids of university students.